KONSEP LABA BERKAH DALAM PERDAGANGAN SYARIAH - Zaenudin Mansyur (Asy-Syari'ah, 2022)
The purpose of this study is to examine the concept of blessing profit that is widely discussed by observers of the Islamic economy which isclaimed to be a very  abstract matter so that measuring it becomes a very difficult activity  to find, but rather the  right criteria to be able to achieve it. Thus, this study uses a descriptive analysis method to examine more deeply the things that must be done by traffickers, both traders and buyers. The results of  this study show that the  criteria that must be carried out by business people as strong evidence  for them in obtaining blessing profits, namely through the preprocessing stage, process, and postprocess. The preprocess stage is required to base its trade attitude with theological values so that its tendency will give birth to a high devotion to the powerful. Meanwhile, the stages of the process strengthen it by instilling an honest, sincere, professional, friendly sosial, and generous attitude. This honest attitude will encourage  the birth of a sincere attitude of both parties and inturngive birth to a professional attitude so that trade activities run smoothly which is characterized by customers increasing from time to time because it is based on the inten silaturrahim and generous of traders and buyers so that the final stage strengthens the acquisition of blessing profits through evaluation of the trading activities carried outby him through the payment of obligations after reaching one nisab.